Prevalence, comorbidities, and profiles of neurodevelopmental disorders according to the DSM-5-TR in children aged 6 years old in a European region - Francés, Lorena; Ruiz, Antoni; Soler, C. Virgínia; Francés, Joan; Caules, Jessica; Hervás, Amaia; Carretero, Carolina; Cardona, Bárbara; Quezada, Elizabeth; Fernández, Alberto; Quintero, Javier (Frontiers in Psychiatry, 2023)
Background: There are no studies that measure the prevalence and real comorbidities of neurodevelopmental disorders (NDDs) according to the DSM-5-TR in 6-year-old children in population and clinical samples or studies that measure them as a whole. The data on the prevalence of these disorders are usually disparate because of the estimation methods (direct/indirect), the type of sample (population/clinical/school) and the ages studied. The initial sample (289 subjects) was representative of the 6-year-old children in Menorca. The patients were divided into two groups based on the criterion of verification of clinical warning signs: clinical or experimental sample (EG) (81 subjects) at risk of NDDs and the control sample (CG) (210 subjects) without risk. A direct clinical assessment of the clinical sample was carried out, and they were administered the Wechsler Intelligence Scale for Children (WISC V), the Clinical Evaluation of Language Fundamentals (CELF-5), the Battery for the evaluation of the processes of revised reading (Batería para la evaluación de los procesos de lectura revisada -PROLEC-R), the Test for the Diagnosis of Basic Mathematical Competences, (TEDI-MATH) and the Developmental Coordination Disorder Questionnaire (DCDQ), among others.Results: A total of 21.5% of the initial sample suffered from an NDD. A total of 2.4% presented autism spectrum disorder (ASD); 14% presented attention deficit hyperactivity disorder (ADHD); 0.34% presented mild intellectual disability; 9.54% presented communication disorder (CD); 10% presented learning disorder with reading difficulties; 5.8% presented learning disorder with difficulties in writing; 3.11% presented learning disorder with difficulties in mathematics; 1% presented transitory tic disorder; 0.34% presented chronic tic disorder, 1% presented Tourette syndrome; 2% presented motor coordination disorder (MCD), and 0.34% presented stereotypic movement disorders.Males were more affected than were females in general, with male/female ORs of 0.14/0.92 for the presence of comorbidities, 0.11/0.88 for combined ADHD, 0.06/0.87 for language disorder, 1.02/1.27 for MCD, and 1.39/1.02 for inattentive ADHD.In disadvantaged contexts, there was a higher prevalence of NDDs and comorbidities. A significant proportion of the sample had not been previously diagnosed (88.6%); therefore, early detection programmes are recommended to identify warning signs and develop policies that help the most disadvantaged sectors of the population.